2013
DOI: 10.1007/s13594-013-0153-2
|View full text |Cite
|
Sign up to set email alerts
|

MilkAMP: a comprehensive database of antimicrobial peptides of dairy origin

Abstract: The number of identified and characterized bioactive peptides derived from milk proteins is increasing. Although many antimicrobial peptides of dairy origin are now well known, important structural and functional information is still missing or unavailable to potential users. The compilation of such information in one centralized resource such as a database would facilitate the study of the potential of these peptides as natural alternatives for food preservation or to help thwart antibiotic resistance in path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(35 citation statements)
references
References 45 publications
0
33
0
2
Order By: Relevance
“…bLfcin showed bactericidal activity against a range of Gram-positive and Gram-negative bacteria [67], whereas hLfcin only exerted bacteriostatic activity [62]. The wide range of activities are shown in Table 3; the MIC as antibacterial, antifungal and anti-protozoarian activities are taken from the milkAMP database [14].…”
Section: In Vitro Antibacterial and Anti-fungal Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…bLfcin showed bactericidal activity against a range of Gram-positive and Gram-negative bacteria [67], whereas hLfcin only exerted bacteriostatic activity [62]. The wide range of activities are shown in Table 3; the MIC as antibacterial, antifungal and anti-protozoarian activities are taken from the milkAMP database [14].…”
Section: In Vitro Antibacterial and Anti-fungal Activitymentioning
confidence: 99%
“…Lfampin exhibits broad antimicrobial action against several Gram-positive and Gram-negative bacteria, yeast and parasites: data taken from the MilkAMP database are reported in Table 6 [14,123]. Although no advanced preclinical trials or applications have yet been reported, the study by Flores et al shows that the combination of ampicillin with LFcin 17-30 or LFampin 265-284 enhanced the inhibitory effect on growth of S. aureus (99.9%) for both peptides, suggesting that a synergistic effect occurs.…”
Section: Lf Derived Peptides: Lactoferrampinmentioning
confidence: 99%
“…Bioactive milk peptides have been reviewed numerous times over recent decades, but no comprehensive database of these peptides exists. A partial database (milk AMP) does exist (Théolier, Jérémie, Ismail, Julie, & Riadh, 2013); however, it includes only antimicrobial peptides and was last updated September 2012. Some milk peptides are present in generic bioactive peptide databases such as the Antihypertensive Peptide Database (AHTPDB) (Kumar, Chaudhary, Sharma, Nagpal, Chauhan, Singh, et al, 2015) and BIOPEP (Minkiewicz, Dziuba, Iwaniak, Dziuba, & Darewicz, 2008); however, these databases were far from comprehensive for milk protein-derived peptides and have not been updated within recent years to our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Since the publication of APD and ANTIMIC, several specialized databases have been established to emphasize certain aspects of natural, synthetic, or recombinant AMPs from a special peptide family (circular peptides, defensins, and thiopeptides) or source (e.g., bacteria, plants, shrimps, amphibians) [15-28]. For example, defensin knowledgebase is dedicated to defensins only, while DADP contains only polypeptides from frogs.…”
Section: Introductionmentioning
confidence: 99%